Penguatan Budaya Pertunjukan Sebagai Atraksi Wisata Melalui Diskusi Partisipatif di Desa Lumba Suhi-suhi Toruan - Denata Rajagukguk; Tio RJ Nadeak; Ade Putera Arif Panjaitan; Mery Silalahi; Wolter P Silalahi; Liyus Waruwu; Debora Purba; Darwin Bastian Ndraha; Apriliana Lase; Arina Manalu; et al. (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This community service activity was conducted in Lumban Suhi-Suhi Toruan Village, Pangururan District, Samosir Regency, focusing on strengthening performing arts as a tourist attraction. The main problems identified were the suboptimal management of cultural performances as tourism assets, indicated by limited performance frequency, unprofessional packaging, lack of regeneration of performers, and limited foreign language skills in communicating with international tourists. This activity aimed to enhance the capacity of the community and village government in developing performing arts through a participatory approach. The method applied was participatory discussion in the form of Focus Group Discussions (FGD), involving community members, village officials, academics, and students. Data were collected through discussion results, field notes, and documentation, and analyzed using a descriptive qualitative approach. The results show an increased collective awareness among participants regarding the potential of performing arts as both an economic asset and a representation of local identity. The discussions produced several strengthening strategies, including scheduling regular performances, involving younger generations, providing English language training, developing multilingual promotional materials, and establishing a foreign-language-speaking tour guide system. The activity also fostered synergy among community members, village government, and academics in formulating more structured and sustainable development plans. Therefore, strengthening performing arts through participatory discussions proved effective in enhancing local capacity and promoting sustainable culture-based village tourism development.